Acoustic Streaming: Probing Cell Deformability via Acoustically Actuated Bubbles (Small 7/2016). Issue 7 (11th February 2016) - Xie, Yuliang; Nama, Nitesh; Li, Peng; Mao, Zhangming; Huang, Po‐Hsun; Zhao, Chenglong; Costanzo, Francesco; Huang, Tony Jun
Abstract : An acoustically actuated, bubble‐based technique is developed to investigate the deformability of cells suspended in microfluidic devices. On page 902, measurements of mechanical biomarkers from multiple cells made by T. J. Huang and co‐workers are conducted in a single experiment, and integrated with other bioanalysis and drug‐screening platforms. It is expected that this technique could provide insights for cell biology studies and biophysical cellular diagnosis.